Azacitidine in patients with WHO-defined AML – Results of 155 patients from the Austrian Azacitidine Registry of the AGMT-Study Group - Pleyer, Lisa (BioMed Central, 2013)
OBJECTIVE: The Austrian Azacitidine Registry is a multi-center database (ClinicalTrials.gov: NCT01595295). The nature and intent of the registry was to gain a comprehensive view of the use, safety and efficacy of the drug in a broad range of AML-patients treated in real-life scenarios. PATIENTS AND METHODS: The sole inclusion criteria were the diagnosis of WHO-AML and treatment with at least one dose of azacitidine. No formal exclusion criteria existed. A total of 155 AML-patients who were mostly unfit/ineligible for intensive chemotherapy, or had progressed despite conventional treatment, were included. True ITT-analyses and exploratory analyses regarding the potential prognostic value of baseline-variables/performance-/comorbidity-/risk-scores on overall survival (OS), were performed. RESULTS: In this cohort of 155 pretreated (60%), and/or comorbid (87%), elderly (45% ≥75 years) AML-patients, azacitidine was well tolerated and efficacious, with an overall response rate (CR, mCR, PR, HI) of 45% in the total cohort (ITT) and 65% in patients evaluable according to IWG-criteria, respectively. Pre-treatment with conventional chemotherapy (P = .113), age ≤/>80 years (P = .853), number of comorbidities (P = .476), and bone marrow (BM) blast count (P = .663) did not influence OS. In multivariate analysis hematologic improvement alone (without the requirement of concomitant bone marrow blast reduction), although currently not regarded as a standard form of response assessment in AML, was sufficient to confer OS benefit (18.9 vs. 6.0 months; P = .0015). Further deepening of response after first response was associated with improved OS (24.7 vs. 13.7 months; P < .001). CONCLUSIONS: In this large cohort of AML-patients treated with azacitidine, age >80 years, number of comorbidities and/or BM-blasts >30% did not adversely impact OS.